IS Success Model for EDMODO E-learning User Satisfaction through TAM on Students - Ridwan Daud Mahande; Jasruddin Jasruddin; Nasir Nasir (Journal of Educational Science and Technology (EST), 2019)
This study aimed to analyze the effect of IS Success Model variable on Edmodo's e-learning user satisfaction partially, both directly and indirectly through the TAM variable. This research was conducted through an ex-post-facto approach to undergraduate students. Data collection instruments used questionnaire and observation. The questionnaire was developed from the technology acceptance model (TAM) and information system (IS) success model. The collected data were analyzed through descriptive statistics and path analysis using IBM SPSS 20 program. The results showed that the three core variables of the IS Success model directly had a significant effect on the two core variables of TAM, and the two core variables of TAM directly affected user satisfaction. Indirectly, the three core variables of IS Success model had a significant effect on user satisfaction through the two core variables of TAM. Service Quality, also, to provide a more significant direct effect on perceived usefulness, also indirectly influenced user satisfaction through perceived usefulness. Perceived ease of use had more significant direct and indirect effects through perceived usefulness on Edmodo e-learning user satisfaction.